COMPLICATIONS AND OUTCOME OF DIPHTHERIA IN ADMITTED PEDIATRIC PATIENTS AT A TERTIARY CARE SETTING IN PESHAWAR - Khan, Muhammad Hussain; Aurakzai, Ahmad Ali; Irshad, Muhammad; Ullah, Ihsan (Journal of Postgraduate Medical Institute, 2018)
Objectives: To determine the frequency of complications of Diphtheria infection in our admitted pediatric patients and their outcome. Methodology: This prospective observational study was conducted at Department of Pediatrics, Lady Reading Hospital, Peshawar. All patients admitted to the isolation unit of Pediatric Department from March 2016 to December 2017 were included in the study. During the study period, a total of 56 patients aged 6 months to 16 years having pharyngeal diphtheria were enrolled. Each patient was closely monitored and evaluated through X-ray chest, complete blood counts, blood chemistry, electrocardiography, cardiac enzymes and echocardiography. Patients were followed for 6 weeks and Diphtheria complications along with their outcome were recorded and analyzed using Microsoft Excel. Results: Out of total 56 patients, 39 (69.64%) were males and 17 (30.35%) were females. Most of them (64.28%) were school age children with age range 5-10 years. Eleven patients (19.64%) out of 56 developed major complications. Among these 09 (16%) had myocarditis and 2 (3.5%) had polyneuropathies. Five patients (8.92%) died during the study period due to myocarditis and severe rhythm disturbance. Conclusion: Cardiac complications of pharyngeal diphtheria were found to be the most common and fatal followed by polyneuropathy.